Technoserve : Mozambique Case Study - World Bank (Washington, DC, 2014)
The innovative approaches and methods that Technoserve Mozambique (TnsMz) has pioneered have become best practice templates for other Tns country operations and, indeed, best practice templates within Mozambique itself, where TnsMz's successes in the cashew, banana, and poultry industries are notably successful. Tns offers no centralized facilities for practicing and refining business skills, but rather serves its clients where one do business, in the rural areas where crops and animals grow. However, it frequently creates partnerships with industry leaders using sites to demonstrate and or train new market entrants in best practices for processing, marketing, logistic management, and quality control. Its programs are designed to stimulate investment, job creation, and local economic activity within commodity-oriented agribusiness sectors, which typically afford only thin profit margins. TnsMz provides incentives in the form of grants or matching grants to change behavior and to introduce new technologies within farm-to-market chains. In this context, this report presents summary, background and context, strategic vision, mission, and targets, TnsMz's distinctive features, brand, and market position, approach to incubation, business model, staffing, network partners, current portfolio strategies, achievements, critical success factors, lessons learned and implications for agribusiness incubators, and future goals.